RAISED INTRAOCULAR PRESSURE AND RECURRENCE OF RETINAL DETACHMENT AS COMPLICATIONS OF EXTERNAL RETINAL DETACHMENT SURGERY - Jawad, Mohammad; Khan, Bilal; Shah, Mir Ali; Qayyum, Iftikhar; Aftab, Mohammad (Journal of Ayub Medical College Abbottabad, 2015)
Background: Patients with Rhegmatogenous retinal detachment may develop raised intraocular pressure and recurrence of retinal detachment when they undergo external retinal detachment surgery. The present study was conducted to determine the postoperative rise in intraocular pressure (IOP) and recurrence of retinal detachment. Methods: The present descriptive study was conducted at Eye department of Lady Reading Hospital, Peshawar on 25 patients of both genders from August 2012 to July 2014. Results: Of the 25 patients, 18 (72%) developed raised IOP in the immediate postoperative period; this figure decreased to 12 (48%) at one week. Following medical or surgical intervention in these 12 cases, there was only 1 (4%) case with mildly raised IOP at two weeks postoperative. Five (20%) cases developed recurrent retinal detachment which later resolved with treatment. There were no significant differences by age or gender. Conclusion: External Retinal Detachment Surgery raised intraocular pressure postoperatively and caused recurrence of retinal detachment. These complications were treated medically and surgically with resolution within two weeks.